Think muscle; Think rhabdomyolysis - Fatimah Lateef; Arunima Gupta (Journal of Acute Disease, 2018)
Rhabdomyolysis is the breakdown of striated muscle cells resulting in leakage of cell matter into the extra-cellular space. It can present with myalgia, muscle weakness and swelling. Episodes of passing of dark tea-coloured urine have also been reported. Raised creatinine kinase is diagnostic of rhabdomyolysis. Raised serum myoglobin levels and presence of myoglobin in the urine (myoglobinuria) help to support the diagnosis. The aetiology for rhabdomyolysis can be both traumatic and non-traumatic. In the case of trauma, individuals with crush injuries trapped in cars or under collapsed buildings , struggling against restraints, immobilized and in the same position for hours due to injuries, comatosed states or positioning during prolonged surgeries and those with high voltage electrical injuries are at increased risk of rhabdomyolysis. Non-traumatic causes of rhabdomyolysis include hyperthermia, metabolic myopathies, drugs and toxins ingestions, electrolyte abnormalities and infections. The mechanism of rhabdomyolysis is often multifactorial. In the case of trauma, direct injury to cell membranes as well as hypoxia from direct compression leading to adenosine triphosphate depletion leads to breakdown of striated muscle cells.. The lysed cells release myoglobin, creatine kinase, urate and phosphate into the interstitium. Direct heme protein-induced toxicity on nephrons can result in acute kidney injury. We report a case of traumatic rhabdomyolysis and share the latest in the literature on the understanding of the subject as well as that of myoglobinuria, with which it is often associated with.